A research study on the hiring preferences of banks in Iloilo City on new graduates - Ates, Sharon Grace V.; Clementir, Joan E.; Maravillosa, Leah F.; Silva, Jonabelle L.; Sullano, Rosyn J. (2003.)
The study focused on the hiring preferences of banks in Iloilo City on new graduates. It involved banks, regardless of what type, which join in the Bangko Sentral ng Pilipinas clearing. As a method of collecting data, the researchers employed the distribution of questionnaires to the prospective respondents. It was also made sure that respondents were bank or personnel managers or other employees who were knowledgeable about the hiring process. The number of respondents were 30, most were male bank managers and other personnel. They composed the 63% of the entire population of respondents. Several factors that the researchers deemed important and could affect the hiring of new graduates were cited. These were gender, age, civil status, physical attributes, the school where the applicant graduated from, scholastic record, background training and the exam and interview rating. The respondents then ranked these factors as to the degree or level of importance in terms of their hiring decisions with regards to new graduates. The research was conducted on the basis of imparting knowledge to the new graduates, especially those who are planning to work in a bank. This would somehow ease the tension or pressure if the future applicants know about the hiring preferences of banks in Iloilo City.
Research Study (Mgt 199 - Management Research) -- [Iloilo City] : University of the Philippines in the Visayas-College of Management, March 21, 2003.